PROFITABILITY, CAPITAL STRUCTURE AND DIVIDEND POLICY EFFECT ON FIRM VALUE USING COMPANY SIZE AS A MODERATING VARIABLE (In the Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange (IDX) during 2015 - 2019 Periods) - Dwi Vina Rahmawati; Akhmad Darmawan; Feti Setyarini; Fatmah Bagis (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study examines the effect of profitability, capital structure and dividend policy on firm value with firm size as a moderating variable. This study's population were all consumer goods industry sector companies listed on the Indonesia Stock Exchange during 2015-2019, which are 63 companies. The sample selection in this study was carried out by purposive sampling. Based on the criteria, 14 companies were used as samples. The research method used in this study is the multiple regression analysis. This study indicates that profitability, capital structure, and dividend policy have a positive and significant effect on firm value. The results of this study also indicate that firm size weakly moderates the effect of dividend policy on firm value, but firm size is unable to moderate the effect of profitability and capital structure on firm value. Keywords: profitability, capital structure, dividend policy, firm value, company size